Primenenie kombinirovannykh oral'nykh kontratseptivov u zhenshchin reproduktivnogo vozrasta s ozhireniem (Ожирение и метаболизм, 2009)
This article assesses the problem of obesity as a risk factor for development of severe metabolic complications and different disorders of reproductive function in women of childbearing age. It is pointed that obesity is associated with high prevalence of hyperandrogenemic and hyperplastic disorders, polycystic ovary syndrome, infertility, complications of pregnancy and childbirth. Article discusses the questions of integrated treatment approach of this category of patients, which include non-drug interventions (rational nutrition, lifestyle modification) as well as the use of medications which lower the insulin resistance and hyperinsulinemia to restore ovary function and the possible use of combined oral contraceptives for correction of anovulation.